Św. Jan Chryzostom, VII Homilia w cyklu Homilii do Listu do Filipian - Latawiec, Zofia (Vox Patrum, 2019)
This study is the first Polish translation of John Chrysostom’s seventh homily in relation to the Letter to the Philippians. The study includes two sections. The first one is a theoretical introduction to St. John’s style, followed by investigation into the origin of the homily. The subject matter of Chrysostom’s work is also discussed. The first part of this study is also systematic analysis of elements showcasing the author’s rhetorical skills. The following part is the translation of aforementioned homily with a philological commentary and comparative analysis of the work in the light of description of its biblical references and its lexical analysis.